Zygomaticomaxillary complex fractures: finding the least complicated surgical approach (A Randomized Clinical Trial) - Lydia N. Melek; Marwa G. Noureldin (BMC, 2023)
Abstract Background Many approaches have been suggested for management of zygomaticomaxillary fractures. Each approach has its own advantages and limitations. Aim of this study The study is intended to compare between the subtarsal approach, conventional transconjuctival approach and the Y- modification of the transconjuctival approach in the management of zygomatico-maxillay complex fractures. Materials and methods Twenty-four patients with age range of 20-50 years requiring open reduction and fixation of a fractured zygomatic complex were randomly divided into three equal groups. Group A: subtarsal approach group, group B: a conventional transconjunctival approach group and group C: Y- modification of the transconjunctival approach group. Intraoperative and postoperative parameters were evaluated. Results As for the exposure time, group C had the longest duration. Easy access to the site of fracture was reached in all groups with no statistically significant difference. During the first 24 h, the pain was only statistically significant between groups A and B with higher pain level in group A. After the first week, pain was significantly higher in groups A and C, with respect to group B. The least edema was observed in group B after 24 h, one week and four weeks postoperatively. Regarding ocular complications, wound healing and sensory nerve function, there was no statistically significant difference between the groups. Scarring was only noticeable in group A patients. Conclusion The transconjunctival approach provides adequate exposure with excellent esthetics and minor complications. The Y-modification also delivers an esthetic access with inconspicuous scar to the frontozygomatic region. Trial registration The trial has been registered on clinicaltrials.gov (ID: NCT05695872).